Categories of context in realist evaluation. (April 2021) - Sheaff, Rod; Doran, Natasha; Harris, Michael; Lang, Iain; Medina-Lara, Antionieta; Fornasiero, Mauro; Ball, Susan; McGregor-Harper, Judith; Bethune, Rob
Realist evaluation has become widespread partly because of its sensitivity to the influence of contexts on policy implementation. In many such evaluations, the range of contexts considered relevant nevertheless remains disparate and under-conceptualised. This article uses findings from a realist evaluation of English Patient Safety Collaboratives during 2015–2018 to develop a realist taxonomy of contexts, differentiating contexts according to how they affect the corresponding policy mechanism. By analysing the main context-mechanism-outcome configurations that made up the English Patient Safety Collaboratives, we derive a taxonomy of the contexts that affected implementation and outcomes. The categories of context were structural (network, hierarchy, market and organisational contexts); resource-based (actors, material, financial); motivational (receptivity, outcome headroom), and temporal (continuity, history and convergence). To the categories found in previous studies, this study adds the three temporal contexts.